2011
DOI: 10.1186/1750-9378-6-5
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Human herpesvirus 8 (HHV-8) and incidence of Kaposi's sarcoma in Iran

Abstract: Seroepidemiological surveys show that the prevalence of human herpesvirus 8 (HHV-8) infection mostly varies in various geographical areas and reflects the local incidence of classic and endemic KS, being widespread in sub-Saharan Africa and Mediterranean countries and uncommon in the USA and Northern Europe. In the Middle East only few populations, such as Ashkenazi and Sephardic groups in Israel, have been adequately evaluated for HHV-8 seroprevalence. Among Iranian population a striking higher seroprevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
32
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 56 publications
(71 reference statements)
5
32
0
1
Order By: Relevance
“…Higher detection rates of HHV‐8 DNA and plasma anti‐HHV‐8‐IgG were found in the hemodialysis patients compared to a sample of apparently healthy people (blood donors and pregnant women, which for purposes of analysis were combined as a single group). This result supports previous data showing the comparatively high prevalence of plasma anti‐HHV‐8 in patients with chronic renal failure when compared to controls from the same country [Qunibi et al, 1998; Regamey et al, 1998; Hsu et al, 2002; Bergallo et al, 2007; Caterino‐de‐Araujo et al, 2007; Lonard et al, 2007; Jalilvand et al, 2011].…”
Section: Discussionsupporting
confidence: 90%
“…Higher detection rates of HHV‐8 DNA and plasma anti‐HHV‐8‐IgG were found in the hemodialysis patients compared to a sample of apparently healthy people (blood donors and pregnant women, which for purposes of analysis were combined as a single group). This result supports previous data showing the comparatively high prevalence of plasma anti‐HHV‐8 in patients with chronic renal failure when compared to controls from the same country [Qunibi et al, 1998; Regamey et al, 1998; Hsu et al, 2002; Bergallo et al, 2007; Caterino‐de‐Araujo et al, 2007; Lonard et al, 2007; Jalilvand et al, 2011].…”
Section: Discussionsupporting
confidence: 90%
“…In Middle Eastern countries, similar seroprevalence rates were reported in Saudi Arabia (2 % in healthy controls, 18 % in renal transplant recipients) [ 4 ] and in Iran (2 % in blood donors, 17 % in hemodialysis patients, 25 % in renal transplant patients) [ 205 ]. In Israel, KSHV seroprevalence among the different Jewish groups was found to correlate with the incidence of KS.…”
Section: Epidemiology Of Kshv Infectionsupporting
confidence: 73%
“…In this study, we evaluated the sero-prevalence, prevalence, and risk factors of HBV, HCV, HTLV-I, and KSHV infections among prisoners in Mashhad, Iran. This study showed higher overall prevalence of HBV, HCV, HTLV-I, and KSHV among prisoners compared to the general population of Iran (9, 36-38). It is possibly because of their behavioral patterns and frequent use of risky behaviors (such as drug abuse, alcohol consumption, and sexual practices).…”
Section: Discussionmentioning
confidence: 48%